Current status and prospects of research on coal mine dust mist condensation and dust reduction efficiency enhancement - Boyang JIANG; Yipei QI; Jiayong ZHANG; Liwen GUO; Jia LI; Yang XIAO (Meitan kexue jishu, 2025)
The problem of coal dust caused by the improvement of mine mechanization and intellectualization is becoming more and more serious. spray is widely used to treat coal dust problems in underground working faces. The coalescence process of dust mist can achieve coal dust settlement, and then alleviate the harm of coal dust to workers’ health and the pressure on safe production. In order to further improve the dust reduction measures at the working face, improve the quality of the underground working environment, optimize the wet dust removal system at the working face of the mine, and accelerate the achievement of the goal of green mining. By reviewing relevant literature at home and abroad, combined with the development history of relevant theories and the current status of practical research, this paper analyzes the research progress of dust mist condensation wet dust removal technology, including the process and mechanism of droplet dust collection, research on coal dust wettability, progress in surfactant optimization, mechanism of internal and external flow field jet fragmentation and atomization, and the development history of nozzles. At the same time, in view of the lack of thorough research on the contact wetting combination sedimentation mechanism of spray dust reduction, insufficient understanding of the atomization behavior of liquid medium under the action of the external flow field in the internal flow field of spray, unclear coupling relationship between various influencing factors of atomization effect, lack of sufficient theoretical support for measures optimization, inconsistency between field application and laboratory results, and other problems, the impact of the impact of the spray on the atomization mechanism, coal dust wettability, surfactant, nozzle atomization characteristics Propose research prospects for on-site applications and other aspects. Research has shown that the prevention and control system for coal dust in China’s mines has begun to take shape. In the future, the focus of research will shift to the study of wetting dust collection mechanism, joint analysis of factors affecting the wettability of deep-seated and multi-angle coal dust, improvement of characterization parameters and measurement methods for atomization and dust reduction effects, optimization of atomization characteristics of dust mist multi-angle nozzles, development of harmless and synergistic surfactants, and popularization of on-site applications.